Implementation of Global Diversity Values in Vocational High School Students - Siti Yumaroh; Suranto (Didaktika: Jurnal Kependidikan, 2024)
Pancasila student profile is the character and competence that Indonesian students must have both in the middle of their studies and when they plunge into society. This research aims to find out how global cultivation at SMK N 6 Surakarta can be applied to learning, school environments, and communities. As an attempt to realise the character of a nation by understanding how cultural differences, languages, and beliefs can affect relationships between individuals, organisations, and states. The methodology of this research is type of research used is qualitative; the subject of research is the deputy head of school, 3 teachers, and 5 students; data collection taken through interviews, observations, and documentation. The results of the study show that cultivating is the value of global sensitivity in SMK N 6 Surakarta can be well embedded, schools can develop further strategies to enhance inclusiveness, strengthen intercultural respect, prepare students to interact positively in an increasingly connected global society.